2020
DOI: 10.5539/elt.v13n10p139
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Skills, Reading Comprehension and Learning Achievement in Vihiga County Kenya. Addressing Constraints and Prospects

Abstract: Prediction skill may be used in reading comprehension passages as encapsulated in interactive approach instruction. Prediction skills assist learners to decode the meaning of comprehension passages by constructing guesses about the contents of texts to be read in comprehension passages. Learners in Vihiga County register low achievement in English language examinations than peers in neighbouring counties over the years. The performance is much weaker in comprehension passages than grammar sections. Although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In Kenya, low language proficiency was evident in results from various studies. In Vihiga County, Anyiendah et al (2020) found that elementary school learners performed worse in English tests than their peers in neighbouring counties over time. In Kisii District, Obunga (2016) found that 3rd graders read below their grade level.…”
Section: Introductionmentioning
confidence: 93%
“…In Kenya, low language proficiency was evident in results from various studies. In Vihiga County, Anyiendah et al (2020) found that elementary school learners performed worse in English tests than their peers in neighbouring counties over time. In Kisii District, Obunga (2016) found that 3rd graders read below their grade level.…”
Section: Introductionmentioning
confidence: 93%